Bioassay of some agricultural chemicals, human drugs and disinfectants on Phytophthora melonis Katsura causing fruit and vine rot of pointed gourd (The Journal of Plant Protection Sciences, 2023)
Some antibiotics, insecticides, disinfectants and antiprotozoal drugs were tested on Phtophthora melonis Katsura  causing fruit and vine rot of pointed gourd in aqueous environment. Antifungal antibiotics viz. validamycin, kasu gamycin, griseofulvin, fluconazole and ketoconazole did not have any pronounced effect on mycelial growth, spo rangia formation and its germination. None of the eight antibiotics used in this study prevented mycelial growth.  No sporangia formation was recorded in five antibiotics viz. streptomycin sulphate + tetracycline hydrchloride,  streptomycin sulphate, oxytetracycline hydrochloride, ofloxacin and norfloxacin at 100 ppm. The insecticide, Pro fenophos prevented sporangia formation and consequently its germination. Copper sulphate (CuSO4, 5H2O) had  adverse effect on mycelial growth and sporangia formation. Potassium permanganate (KMnO4), Savlon, Dettol and  tinidazole were not good inhibitor for P. melonis. Sporangia did not form in water containing 0.0125g/L chloro quin phosphate - an antiprotozoal drug.
Keywords: Antibiotic; antiprotozoal drug; bioassay study; disinfectan